Antara Kepastian dan Keadilan: Perspektif Hukum Islam terhadap Legalisasi Dokumen Asing dan Peran Notaris - Lestari, Kory Febrina (STAINI Press, 2025)
The ratification of the Apostille Convention through Presidential Regulation Number 2 of 2021 marks the transformation of the foreign public document legalization system in Indonesia. This change has a direct impact on the authority and function of notaries, which previously played a central role in the legalization process. In the context of Islamic law, this transformation raises ethical and philosophical questions about the balance between legal certainty and substantive justice. This study uses a normative-philosophical approach with qualitative analysis of laws and regulations, legal doctrines, and Radbruch Formula theory as the main analytical framework. This study also links the values of maqāṣid al-sharī'ah to assess the alignment of the policy of legalization of foreign documents with the principles of benefit and justice in Islamic law. The results of the study show that the policy of implementing the Apostille tends to prioritize efficiency and certainty of formal law, but has the potential to ignore the function of the notary as a guardian of justice and integrity of public documents. It was also found that there was an overlap of authority and a vacuum of norms that demanded a rearrangement of notary regulations. From the perspective of Islamic law, the dominance of legal certainty without considering the dimensions of justice and benefits has the potential to cause an imbalance in legal values. Therefore, the reconstruction of the role of the notary needs to be directed at the harmonization of values between haqq (truth) and 'adl (justice) as an implementation of maqāṣid al-sharī'ah in the national legal system.